MYSTERY BOX TRANSACTIONS ON THE TOKOPEDIA MARKETPLACE: A LEGAL ANALYSIS OF CONSUMER PROTECTION IN INDONESIAN CIVIL LAW - Kinara Angelia Yuwanda Pratiwi (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2025)
With the advancement of information technology in Indonesia, various new business models have emerged that utilize digital platforms as the primary medium for economic activities. One notable example is online shopping applications that enable the purchase of goods through an entirely digital process, including payment methods. However, the buying and selling practice of mystery boxes raises legal issues, particularly regarding consumer protection. This research examines the validity of mystery box transactions from the perspective of Indonesian civil law, focusing on Article 1320 of the Civil Code concerning the legal requirements of an agreement. The findings indicate that the object of mystery box transactions is uncertain, which may lead to elements of fraud. This practice also contradicts Law Number 8 of 1999 on Consumer Protection, which mandates that business actors provide clear, accurate, and honest information about the goods or services offered. The research method used is normative-juridical, employing a statutory and case approach. The study is descriptive-analytical in nature and aims to provide a comprehensive understanding of the legal issues surrounding mystery box practices and their implications for consumer protection.